2003
DOI: 10.1109/ted.2002.806476
|View full text |Cite
|
Sign up to set email alerts
|

Fully depleted, back-illuminated charge-coupled devices fabricated on high-resistivity silicon

Abstract: Abstract-Charge-coupled devices (CCD's) have been fabricated on high-resistivity, n-type silicon. The resistivity, on the order of 10,000 Ω-cm, allows for depletion depths of several hundred microns. Fully-depleted, back-illuminated operation is achieved by the application of a bias voltage to a ohmic contact on the wafer back side consisting of a thin in-situ doped polycrystalline silicon layer capped by indium tin oxide and silicon dioxide. This thin contact allows for good short wavelength response, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
248
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(253 citation statements)
references
References 55 publications
2
248
0
3
Order By: Relevance
“…In previous work [1] [10] it has been shown that for these CCDs the spatial variance resulting from diffusion (σ 2 d ) depends on the substrate voltage (V sub ) used to obtain the depletion. For example if V sub is reduced, allowing extra diffusion in the CCD, the image introduced by the reduction of V sub from V B to V A can be quantified by looking at the difference between the two Fourier spectra.…”
Section: Experimental Setup and Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous work [1] [10] it has been shown that for these CCDs the spatial variance resulting from diffusion (σ 2 d ) depends on the substrate voltage (V sub ) used to obtain the depletion. For example if V sub is reduced, allowing extra diffusion in the CCD, the image introduced by the reduction of V sub from V B to V A can be quantified by looking at the difference between the two Fourier spectra.…”
Section: Experimental Setup and Measurementmentioning
confidence: 99%
“…where α is depends on temperature, drift distance and charge of the carries [1]. This translates into the relation…”
Section: Experimental Setup and Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…These devices have high detection efficiency, low noise, good spatial resolution, and low dark current. Furthermore, thick CCDs with increased detection mass enable their use as particle detectors [17]. Using this technology, the DAMIC search for cold dark matter has been deployed at Snolab [10].…”
Section: Introductionmentioning
confidence: 99%